Developing an algorithm to illustrate the likelihood of the dissatisfaction rate with relation to the indoor temperature in naturally ventilated classrooms. (January 2017) - Montazami, Azadeh; Gaterell, Mark; Nicol, Fergus; Lumley, Mark; Thoua, Chryssa
Abstract: There is a direct link between the attainment of children at school and the thermal conditions in classrooms and there are guidelines in place to help designers provide the most effective thermal conditions. However, results from thermal comfort surveys and the collection of the perception of 662 pupils, aged between 8 and 11 in 27 naturally ventilated classrooms from eight primary schools located in the West Midlands, UK during the cooling seasons of 2014 and 2015 suggest that simply designing to a threshold comfort temperature might not be enough to ensure the most effective learning environments are delivered. Indeed, these results confirm that children's threshold comfort temperatures are at least 3 °C lower than adults during cooling seasons in a typical free running UK primary school classroom. Such a difference is important as it is teachers that almost invariably control internal comfort conditions and in adjusting to meet their own preferences might not deliver the most effective learning environments. Consequently, an algorithm has been developed that allows the likely satisfaction rate of children in relation to the indoor temperature in a primary school classroom to be mapped explicitly and provides the basis for comparing differences in satisfaction between adults and children in the same space. The use of this tool can further help designers and teachers deliver and control classroom environments in a way that maximises educational performance. Highlights: Thermal conditions of naturally ventilated schools assessed during cooling seasons. Results show that children's thermal perception is up to 3 K different from adults. An algorithm developed to predict children's thermal dissatisfaction rate. Children's thermal perception affected by their behaviour; environmental and personal. Teachers should be trained to control classroom considering children's perceptions.